Early Experience With Endovascular Aneurysm Sealing in Combination With Parallel Grafts for the Treatment of Complex Abdominal Aneurysms: The ASCEND Registry. (December 2017) - Thompson, Matt; Youssef, Marwan; Jacob, Rudolf; Zerwes, Sebastian; Reijnen, Michel; Szopinski, Piotr; Berg, Patrick; Oszkinis, Grzegorz; Holden, Andrew
Purpose: To report the results of the ASCEND Registry of cases involving endovascular aneurysm sealing (EVAS) in combination with chimney grafts (chEVAS) for the treatment of para- and juxtarenal aortic aneurysms (AAA).Methods: A retrospective, multicenter registry established in 8 vascular centers between 2013 and 2016 recorded the treatment results and follow-up of chEVAS procedures for nonruptured AAAs; data were analyzed using standardized outcome measures. In the observation period, 154 patients (mean age 72.3±7.7 years; 124 men) underwent elective treatment for de novo juxtarenal and pararenal aneurysms and formed the study group.Results: Sixty-two (40.3%) of the cohort were treated using a single parallel graft, 54 (35.1%) with double chimneys, 27 (17.5%) with triple chimneys, and 11 (7.1%) with 4 chimneys. The 30-day mortality was 2.8%, and there were 4 perioperative strokes (1 fatal). At 1 year, the freedom from all-cause mortality was 89.8% and the freedom from aneurysm-related mortality was 94.3%. There were 3 endoleaks within 90 days of the procedure, one type Ia and 2 type Ib. The freedom from type Ia endoleaks was 95.7% at 1 year. There were no types II or III endoleaks in this series; the freedom from all endoleaks was 94.2% at 1 year. Freedom from reintervention at 1 year was 89.2%. Target vessel patency rates at 1 year were 97.7%, 99.3%, 100%, and 100% for the left renal, right renal, superior mesenteric artery, and celiac axis stents, respectively.Conclusion: The ASCEND Registry supports a proof of concept for the use of polymer technology and EVAS with parallel grafts in managing patients with complex aortic disease. The future role of chEVAS will be defined by studies that assess mid- to long-term durability.